2021
DOI: 10.29040/jie.v5i1.2118
|View full text |Cite
|
Sign up to set email alerts
|

Minat Investasi di Kalangan Mahasiswa Generasi Milenial di Surakarta

Abstract: This research aims to see how the influence of capital market knowledge and returns on student investment interest. This research was conducted using quantitative methods with sample size of 120 respondents. The analysis used is multiple linear regression analysis. The results of this research indicated that capital knowledge has a significant effect on student investment interest, When student understand about capital market knowledge deeply, it willl increase the student interest on invetsment. Return also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…On the other hand, the more an individual has a negative assessment, the more likely the individual will have an unfavorable attitude toward that behavior (Ajzen, 2020). Likewise, research carried out (Pamikatsih & Susanti, 2021) revealed that there is a negative and significant influence on risk perception and research carried out by Nandar, 2018 revealed that risk perception has an insignificant negative effect on interest in investing in the capital market.…”
Section: The Influence Of Investment Risk Perceptions On Ubm Students...mentioning
confidence: 99%
“…On the other hand, the more an individual has a negative assessment, the more likely the individual will have an unfavorable attitude toward that behavior (Ajzen, 2020). Likewise, research carried out (Pamikatsih & Susanti, 2021) revealed that there is a negative and significant influence on risk perception and research carried out by Nandar, 2018 revealed that risk perception has an insignificant negative effect on interest in investing in the capital market.…”
Section: The Influence Of Investment Risk Perceptions On Ubm Students...mentioning
confidence: 99%
“…Perkembangan kemajuan angka SID yang terjadi tidak signifikan sesuai dengan jumlah mahasiswa yang aktif. Berdasarkan fenomena yang ada penulis melakukan penelitian untuk mengetahui faktor yang mempengaruhi minat investasi di kalangan gent z. Banyak peneliti yang meneliti mengenai minat investasi (Hutapea, R Sondang ;Dewi, 2021) mengemukakan bahwa Minat investasi di pengaruhi oleh motivasi dan pengetahuan investasi, sedangkan menurut (Pangestika & Rusliati, 2019) mengemukakan bahwa minat invetasi di pengaruhi oleh literasi dan efikasi keuangan (Pamikatsih & Susanti, 2021) salah satu minat investasi dikalangan mahasiswa adalah return atau keuntungan. (Wardani & Komara, 2021) menjabarkan ada beberapa yang mempengaruhi minat investasi diantaranya motivasi, return, resiko, modal minimal dan pelatihan.…”
Section: Sid Fakultas Ekonomi 2018-2021unclassified
“…Variabel dependen penelitian ini adalah minat investasi yang diukur dengan dua pertanyaan terkait ketersediaan inforamsi dan minat investasi (Pamikatsih dan Susanti, 2021). Baik variabel independen maupun dependen diukur dengan menggunakan skala linkert 1-5, yang menunjukkan 1 untuk "sangat tidak setuju" dan 5 untuk "sangat setuju".…”
Section: Illusion Of Controlunclassified